PENGARUH PROGRAM PLP 2 TERHADAP PENGEMBANGAN KOMPETENSI PROFESIONAL CALON GURU - Ahmad; Hasjumaeni; Elsa Indriani; Farid Muhammad; Maya Musfira; Helda Kirana; Lisna Sari; Sahrul; Rafil Andika R; Muh. Arfha; Sarnita; Nur Juwana; Mirda Ramadani; Muh. Rifky; Iis Ariska; Syahwa Regina; Eka Lestari; Sukirman; Kastan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of the School Field Introduction Program (PLP) 2 on the development of prospective teachers’ professional competence. This study employed a quantitative approach using a survey method. The research population consisted of students in educational study programs who had participated in the PLP 2 Program. The sample comprised 120 respondents selected using purposive sampling techniques. Data were collected through the distribution of questionnaires using a Likert scale to measure the implementation of the PLP 2 Program and the level of prospective teachers’ professional competence. The data analysis techniques included descriptive statistical analysis, validity testing, reliability testing, normality testing, and simple linear regression analysis with the assistance of IBM SPSS Statistics. The results of the study indicate that the PLP 2 Program has a positive and significant effect on the development of prospective teachers’ professional competence. This is evidenced by a regression coefficient value of 0.721 and a significance value of 0.000 < 0.05. In addition, the coefficient of determination (R²) value of 0.612 shows that the PLP 2 Program contributes 61.2% to the development of prospective teachers’ professional competence, while the remaining percentage is influenced by other factors outside the scope of this study. The findings reveal that teaching practice activities, preparation of learning tools, classroom management, and the use of instructional media in the PLP 2 Program are able to improve students’ mastery of subject matter, teaching skills, communication abilities, and professional readiness as competent prospective teachers who are prepared to face the world of education.